Biochemical Profiling of Inflammatory and Metabolic Markers in Reproductive-Age Women with Endometriosis - Hanana Hameed, Aaisha Qadir, Tariq Hussain, Waqas Qurshi, Arifa Inayat, Nosheen Sikandar Baloch (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Endometriosis is a chronic gynecological disorder characterized by the ectopic presence of endometrial tissue, commonly presenting with pelvic pain, dysmenorrhea, and infertility. Increasing evidence suggests that endometriosis is a systemic disease involving chronic inflammation and metabolic dysfunction, yet data from South Asian populations remain limited. Objective: To assess the biochemical profile of inflammatory and metabolic markers in reproductive-age women with endometriosis and compare them with healthy controls. Methods: This cross-sectional study was conducted from May 2022 to February 2023 at Bolan Medical Complex Hospital and the Gynecology and Obstetrics Department, Unit 3, Civil Hospital Quetta. A total of 120 women aged 18–45 years were enrolled, including 80 women with laparoscopically confirmed endometriosis and 40 healthy controls. Serum levels of hs-CRP, IL-6, TNF-α, fasting insulin, glucose, lipid profile, and HOMA-IR were measured. Statistical analysis was performed using SPSS version 26.0. Results: Inflammatory markers were significantly elevated in women with endometriosis: hs-CRP (6.72 ± 1.18 vs. 3.25 ± 0.94 mg/L), IL-6 (7.94 ± 2.43 vs. 3.37 ± 1.12 pg/mL), and TNF-α (13.12 ± 3.45 vs. 8.24 ± 2.21 pg/mL) (all p < 0.001). Metabolic disturbances were also noted, with increased fasting insulin, glucose, and HOMA-IR values. Triglycerides were elevated and HDL-C levels were significantly reduced in the endometriosis group. Correlation analysis showed positive associations between disease severity and both inflammatory markers and insulin resistance. Conclusion: Endometriosis in reproductive-age women is associated with systemic inflammation and metabolic dysfunction, with a clear correlation between biochemical abnormalities and disease severity. These findings support the need for a multidisciplinary approach in the diagnosis and management of endometriosis, integrating metabolic and inflammatory monitoring. Keywords: Endometriosis, inflammation, metabolic dysfunction, HOMA-IR, cytokines, reproductive-age women, hs-CRP, IL-6, TNF-α.